2006
DOI: 10.1523/jneurosci.2659-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Function of C-Fibers in Patients with Diabetic Neuropathy

Abstract: The mechanisms underlying the development of painful and nonpainful neuropathy associated with diabetes mellitus are unclear. We have obtained microneurographic recordings from unmyelinated fibers in eight patients with diabetes mellitus, five with painful neuropathy, and three with neuropathy without pain. All eight patients had large-fiber neuropathy, and seven patients had pathological thermal thresholds in their feet, indicating the involvement of small-caliber nerve fibers. A total of 163 C-fibers were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
102
4
11

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(126 citation statements)
references
References 47 publications
9
102
4
11
Order By: Relevance
“…An abnormal function of C-fibers has recently been demonstrated by microneurographic recordings in patients with diabetic neuropathy (8). The extensive nerve fiber loss in the subepidermal nerve plexus seen in our sample of diabetic patients might represent abnormal function of C-fibers' morphologic counterpart.…”
mentioning
confidence: 49%
“…An abnormal function of C-fibers has recently been demonstrated by microneurographic recordings in patients with diabetic neuropathy (8). The extensive nerve fiber loss in the subepidermal nerve plexus seen in our sample of diabetic patients might represent abnormal function of C-fibers' morphologic counterpart.…”
mentioning
confidence: 49%
“…Recent studies of intraepidermal nerve fibers (IENFs) showed that severe loss of IENF was associated with the presence of neuropathic pain only in patients with little or no objective sign of neuropathy, which suggests that different mechanisms underpin the genesis of pain at various stages of neuropathy [32]. Small-fiber neuropathy in diabetes may also affect receptive properties of nociceptors, which impairs mechano-responsive nociceptors and possibly induces neuropathic pain [20]. Some genetic factor may also intervene in the occurrence of neuropathic pains [33].…”
Section: Discussionmentioning
confidence: 99%
“…Otros métodos diagnósticos de neuropatía de fibras delgadas como los estudios de función autonómica y la biopsia cutánea con cuantificación de la densidad de fibras epidérmi-cas son complementarios y han sido validadas en múltiples estudios 14,19 . La microneurografía, desarrollada en Suecia y Alemania a fines de la década 1960-69, es una herramienta de mucho valor en la comprensión de la función de aferentes delgados en sujetos normales 5 , así como en la detección de anomalías funcionales en pacientes con neuropatía dolorosa [20][21][22] . Los estudios fisiológicos han permitido inferir el tipo de receptor a partir de las propiedades bioeléctricas del axón: fibras que demuestran un marcado enlentecimiento asociado a la actividad corresponden a nociceptores, mientras que aquellos que se enlentecen en forma moderada son termoreceptores o fibras simpáticas eferentes, mientras los que se enlentecen en forma muy discreta son probablemente mecanoreceptores de bajo umbral.…”
Section: Discussionunclassified